FREQUENCY OF DIFFERENT CAUSES OF MASTALGIA WITHOUT NIPPLE DISCHARGE AMONG WOMEN PRESENTING AT TERTIARY CARE HOSPITAL - JAWAD , J; ZAHEER , F; JAWAD , W (Biological and Clinical Sciences Research Journal, 2024)
Mastalgia, or breast pain, is a common complaint among women, often impacting quality of life and requiring clinical attention. Understanding the underlying causes of mastalgia is essential to guide management and improve patient outcomes. Objective: The objective of this study was to determine the frequency and associated causes of mastalgia in women presenting to a tertiary care hospital. Methods: This cross-sectional study was conducted at the Department of Surgery, Civil Hospital, Karachi, from March 1, 2023, to August 30, 2023, after obtaining ethical approval from the institutional review board. A total of 176 female patients aged 18–49 years with complaints of mastalgia were included in the study through non-probability consecutive sampling. Both married and unmarried women were enrolled, and data were collected on demographic variables, lifestyle factors, and psychological factors. Statistical analysis was performed to evaluate associations between causes and mastalgia severity. Results: The most common causes of mastalgia identified were caffeine consumption (56%), depression (57%), and smoking (49%). Significant associations were found between mastalgia severity and both smoking (p=0.002) and caffeine consumption (p=0.003). Smokers and caffeine consumers reported higher levels of pain severity. Conclusion: Mastalgia is frequently associated with modifiable lifestyle factors such as smoking and caffeine intake, as well as psychological factors like depression. Addressing these factors may help manage and reduce the severity of mastalgia in affected patients.